Sectoral Classification And Regional Imbalance Of Mamminasata National Strategic Area - Nanda, Devi Aria; Taufiqqurrachman, Fahrizal (Trunojoyo University of Madura, 2024)
This study aims to analyze the economic structure in the Mamminasata National Strategic Area by using quantitative research methods, based on data sources from the Central Bureau of Statistics using 3 analyses namely Location Quotient, Klassen Typology, and Williamson Index. The results of this study show that there are no significant changes in the economic sector in KSN Mamminasata between 2018 and 2022. Although there was a decline in 2020 due to the Covid-19 pandemic, economic growth in the region increased again in 2021. The Klassen Typology analysis shows that Makassar City is categorized as a fast-developing and fast-growing area, while Maros Regency and Sungguminasa Regency are categorized as fast-growing areas, Takalar Regency as a developed but depressed area. The Williamson Index shows that development inequality in KSN mamminasata is stabilizing and even decreasing from 2018 to 2022. Despite some challenges, KSN Mamminasata shows the potential for positive and sustainable economic growth.